Synthesis and characterization of unsaturated polyesters for use in multi-vesiculated particles (MVPs) - Simpson, Jaylin Mitch (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2010.